Differential expression of feeding-related hypothalamic neuropeptides in the first generation of quails divergently selected for low or high feed efficiency. (August 2016) - Blankenship, Kaley; Gilley, Alex; Piekarski, Alissa; Orlowski, Sara; Greene, Elizabeth; Bottje, Walter; Anthony, Nicholas; Dridi, Sami
Abstract: Livestock and poultry sectors are facing a combination of challenges, including a substantial increase in global demand for high quality animal protein, general droughts and steady rise in animal feed cost. Thus feed efficiency (FE), which defines the animal's ability to convert feed into body weight, is a vital economic and agricultural trait. Genetic selection for FE has been largely used in chickens and has been applied without knowledge of the underlying molecular mechanisms. Although it has made tremendous progress (breast yield, growth rate, egg production), there have been a number of undesirable changes such as metabolic disorders. In the present study we divergently selected male and female quail for high and low FE and we aimed to characterize the molecular basis of these differences at the central level, with the long-term goal of maximizing FE and avoiding the unfavorable consequences. The FE phenotype in first generation quails seemed to be achieved by reduced feed intake in female and increased body weight gain in males. At the molecular level, we found that the expression of feeding-related hypothalamic genes is gender- and line-dependent. Indeed, the expression of NPY, POMC, CART, CRH, melanocortin system (MC1R, MC2R, MC4R, MC5R), ORX, mTOR and ACCα was significantly decreased, however ORXR1/2, AMPKα1, S6K1 and STAT1, 5 and 6 were increased in high compared to low FE males ( P < 0.05). These genes did not differ between the two female lines. ADPN gene expression was higher and its receptor Adip-R1 was lower in LFE compared to HFE females ( P < 0.05). In male however, although there was no difference in ADPN gene expression between the genotypes, Adip-R1 and Adip-R2 mRNA abundances were higher in the LFE compared to HFE line ( P < 0.05). This study identified several key central feeding-related genes that are differentially expressed between low and high FE male and female quails which might explain the differences in feed intake/body weight gain observed between the two lines. Of particular interest, we provided novel insights into central AMPK–mTOR–ACC transcriptional differences between low and high FE quail which may open new research avenues on their roles in the regulation of energy balance and FE in poultry and livestock species. Highlights: Divergent selection of male and female quails for low and high feed efficiency (FE) The expression of feeding-related hypothalamic neuropeptides is gender- and line-dependent. Identification of AMPK–mTOR–ACC as a potential molecular signature involved in the difference of FE